Upregulation of LncRNA‐HIT promotes migration and invasion of non‐small cell lung cancer cells by association with ZEB1. (27th October 2016) - Jia, Xiaojing; Wang, Zhicheng; Qiu, Ling; Yang, Yanming; Wang, Yunlong; Chen, Zhishen; Liu, Zhongshan; Yu, Lei
Abstract: Lung cancer is the most common solid tumor and the leading cause of cancer‐related mortality worldwide. Non‐small cell lung cancer (NSCLC) accounts for approximately 80% of all lung cancer cases. The main reason of lung cancer‐related deaths is due to tumor metastasis. But, the mechanisms of NSCLC metastasis remains poorly understood. LncRNAs play pivotal roles in multiple biological processes. LncRNA‐HIT (HOXA transcript induced by TGF β ) was recently identified. LncRNA‐HIT promotes cell migration, invasion, tumor growth, and metastasis. However, the detailed role of lncRNA‐HIT in NSCLC remains unknown. In this study, for the first time, we revealed a novel role of lncRNA‐HIT in the migration and invasion of NSCLC cells. The expression of lncRNA‐HIT was significantly upregulated in NSCLC tissues and cell lines, and the expression level of lncRNA‐HIT correlates with advanced disease stage and predicts unfavorable prognosis of NSCLC patients. Functional assays demonstrated that lncRNA‐HIT markedly increased the ability of NSCLC cells to migrate and invade. Furthermore, the molecular mechanism by which lncRNA‐HIT affects NSCLC cells was associated with regulation of ZEB1 stability. LncRNA‐HIT functions as a prometastasis oncogene by directly associating with ZEB1 to regulate NSCLC. The interaction of lncRNA‐HIT and ZEB1 may be a potential target for NSCLC therapy. Abstract : The expression level of lncRNA‐HIT correlates with advanced disease stage and predicts unfavorable prognosis of NSCLC patients. lncRNA‐HIT affects the migration and invasion of NSCLC cells through association with regulation of ZEB1 stability.